Superalloys 1988 (Sixth International Symposium) 1988
DOI: 10.7449/1988/superalloys_1988_3_12
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Damage Tolerant Microstructure for Inconel 718 Turbine Disk Material

Abstract: A new modified heat treatment has been developed for Inconel 718.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 6 publications
0
26
1
Order By: Relevance
“…This occurs during homogenization and HIP treatments due to Nb-rich ′′ dissolution, as mentioned earlier. However, as relative amounts of ′′ decrease during HIP treatment, carbide formation slows and the phase begins to dissolve through Ostwald ripening [34]. Specimens that undergo hot isostatic pressing after homogenization contain the γ matrix phase, as well as larger MC-carbide and δ phase precipitates labeled 1, 2, and 3 in Figure 7a, respectively.…”
Section: Microstructural Development Of Heat Treated Inconel 718mentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs during homogenization and HIP treatments due to Nb-rich ′′ dissolution, as mentioned earlier. However, as relative amounts of ′′ decrease during HIP treatment, carbide formation slows and the phase begins to dissolve through Ostwald ripening [34]. Specimens that undergo hot isostatic pressing after homogenization contain the γ matrix phase, as well as larger MC-carbide and δ phase precipitates labeled 1, 2, and 3 in Figure 7a, respectively.…”
Section: Microstructural Development Of Heat Treated Inconel 718mentioning
confidence: 99%
“…The ′′ and δ phases dissolve at temperatures above 1032 °C [34]. Dissolution of ′′ stimulates the growth of MC-carbides during HIP treatment [13].…”
Section: Microstructural Development Of Heat Treated Inconel 718mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a microstructural design philosophy has been successfully developed that is aimed at improving the damage tolerance of conventional disc materials. 3 Damage tolerance, by definition, is the ability of the disc material to exhibit greater resistance to the growth of inherent or service induced flaws under creep and/or fatigue loading conditions, while still maintaming adequate low cycle fatigue pro erties, tensile strength, as well as stress rupture strength. !…”
Section: Introductionmentioning
confidence: 99%
“…But, it was reported that δ-phase of globular morphology was promising for fatigue properties [19][20]. A lot of studies were performed about heat treatment for enhancement of mechanical properties, however, many problems are still remaining about δ/γ″/γ′-phase control, grain size and precipitation free zone(PFZ) [21,22].…”
Section: Introductionmentioning
confidence: 99%